Paget-Schroetter Syndrome secondary to anomalous right-sided aortic arch: A case report - Katrina Pardo; Sofia Steger; Edgar Galinanes; Juan Carlos Pereda (Annals of Vascular Surgery - Brief Reports and Innovations)
Thoracic Outlet Syndrome (TOS) is a rare condition, with an estimated prevalence of about 3 in 100,000 individuals.1 Venogenic TOS, also referred to as Paget-Schroetter Syndrome (PSS), is rarer than neurogenic TOS with an estimated prevalence of 1 in 100,000.1 In this case report, we present a rare case of PSS secondary to an anomalous right-sided aortic arch with branching anomalies, which are described poorly in the literature. The patient, a 41-year-old male with no significant past medical history, presented with classic PSS symptoms that include left neck swelling and pain, intermittent numbness, and swelling in the left arm. Following admission, a chest CT with contrast revealed a right-sided aortic arch along with a left common carotid artery and left subclavian artery that share a common trunk. Ultrasound revealed thrombosis of the left subclavian and innominate veins consistent with PSS. He underwent an aspiration thrombectomy and catheter-directed thrombolytic therapy. The patient is currently symptom-free and successfully managed in the short term with anticoagulation therapy.